A Retrospective Study to Investigate the Relationship Between Body Mass Index and Hemodynamic Characteristics in Hypertensive Patients - Wenqi Xiao; Ping Han; Liping Song; Jingwen Yang; Lin Zhou; Xiangning Deng; Zheng J. Ma; Yukun Lang; Hai Zhao; Yuzhuo Zhao; Hui Chen; Wenjing Zhang; et al. (The Journal of Clinical Hypertension)
ABSTRACT The relationship between hemodynamic parameters and body mass index (BMI) in the context of blood pressure regulation in hypertension is unclear. Here, we analyzed data from 1368 uncontrolled hypertensive patients, including key hemodynamic indicators such as heart rate (HR), cardiac index (CI), arterial stiffness (AS), systemic vascular resistance index (SVRI), and thoracic blood ratio (TBR). In this cohort, the average BMI across all hypertension patients was 26.859 ± 3.897 (kg/m2), with obese patients (BMI ≥ 28 kg/m2) averaging 31.01 ± 2.87 kg/m2 and non‐obese (BMI<28 kg/m2) averaging 24.70 ± 2.28 kg/m2. Younger obese patients exhibited higher diastolic pressures than non‐obese peers (p < 0.01). Hemodynamic analysis showed obese patients had increased HR and SVRI but lower CI and AS (p < 0.01). Hypertensive males aged under 60 with obesity displayed a more prominent peripheral vascular phenotype (p < 0.05) and volemic phenotype (p < 0.01) than non‐obese males. Obese females aged under 60 showed a higher incidence of cardiac phenotype (p < 0.01). Across genders, obese hypertensive patients aged over 60 had a greater prevalence of volemic phenotype than non‐obese patients (p < 0.05, p < 0.01, respectively). BMI inversely correlated with CI and positively with SVRI across age and gender categories (p < 0.01). Taken together, we find that patients with hypertension exhibit diverse hemodynamic profiles, and BMI significantly correlates with hemodynamic parameters such as SVRI and CI. Our research identifies BMI as a valuable target for personalized hypertension treatment.